Violence in the language of popular tales: myths, reality and emotions - Úcar Ventura, Pilar (2018)
All through History, many authors have been the ones to reflect the popular imaginary as midpoint between myth and reality. Some traditional talesand contemporary narrations invite us to a more profound reading below the formal surface and show us a mosaic made from past times realities that nowadays are still present. Language is the mean of expression to make patent certain distortions that have been taking place throughout time: verbal violence, anomalies in idiomatic registers, polysemic ambiguity; fantasy and reality, emotions, magic, dreams and definitely, culture which is transported to well-known texts. Maybe, it would be convenient to approximate even more myths to reality in order to pull aesthetic pleasure and popular wisdom out. In order to do that, we are going to analyse in which way the linguistic force is shown in some literary examples.